A friction-based connection for retrofitting RC frames by steel braced frames. (April 2020) - Javadi, Pasha; Tizchang, Ali; GhafourianHesami, AmirHosein; Askari, MohammadJavad
Abstract: This paper presents a new connection for the installation of steel braced frames inside existing reinforced concrete (RC) frames. The proposed connection is called a "clamp-shaped connection" according to its action which is based on friction mechanism. In this connection, by inserting clamping forces on lateral faces of an existing RC beam, the required direct shear resistance between the existing RC frame and retrofitting steel braced frame is provided. The clamp-shaped connection mainly consists of high-strength grout, steel plates, high-strength bars, and clamp-shaped steel arms, that are majorly made and assembled in a manufactory. The benefit of the proposed technique is that it does not require any anchorage devices and minimizes disturbing retrofitting operations at a building site. In this study, four one-bay one-story RC frames are tested to verify the efficiency of the proposed clamp-shaped connection. The scale factor of the test specimens is 1/3 ~ 1/4, to model a low-rise RC building. One specimen is non-retrofitted, and three specimens are retrofitted by steel braced frames. The proposed clamp-shaped connection increases the direct shear resistance at the top of the installed steel braced frames. Simplified equations are proposed to estimate the direct shear resistance of the proposed connection. The experimental results confirm the accuracy of the suggested simplified calculations.